Drifting as Consolation in Michael Ondaatje’s Anil’s Ghost - Judith MISRAHI-BARAK (E-REA)
Michael Ondaatje’s Anil’s Ghost deals with the exhumation and identification of bones in the context of the civil war in Sri Lanka. Sent by a human rights group to investigate mass burials, Sri Lankan-born and North American-educated Anil Tissera returns to her native island as a forensic anthropologist after 15 years away. Invested as she is in her job, Anil needs time to authorize herself to be affected by what she uncovers. The reconstruction of her relationship with the excruciating history of the island takes unusual narrative shapes in the novel, which has been criticized for meandering along too many digressions and for “drifting […] away from the book’s essential business” (Maslin 11). As I investigate what can be referred to as literary drifting, I offer the hypothesis that such drifting is the route the novel takes to steer the protagonist and the readers from desolation to consolation. I argue that, far from diverting us from the main forensic purpose of the book, Ondaatje’s literary drifting contributes to creating a new space and time for the desolate and the inconsolable, as if solace could only be found in the relational engagement with a community.